The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acsaem.9b00250
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Sodium Ion Transfer at the Na/NASICON Interface Improved by Uniaxial Compression

Abstract: A robust ceramic solid electrolyte with high ionic conductivity is a key component for all-solid-state batteries (ASSBs). In terms of the demand for high-energy-density storage, researchers have been tackling various challenges to use metal anodes, where a fundamental understanding on the metal/solid electrolyte interface is of particular importance. The Na+ superionic conductor, so-called NASICON, has high potential for application to ASSBs with a Na anode due to its high Na+ ion conductivity at room temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 51 publications
1
56
0
Order By: Relevance
“…Moreover, the total resistance starts to decrease until cycling at 1.0 mA cm −2 (Figure 3f and Figure S11c, Supporting Information) and ultimately shows a high CCD of 1.4 mA cm −2 , which to our best knowledge is the top‐level among reported NASICON‐based SSEs in published literatures up to now (Figure 3g). [ 37–41 ] It also shows excellent long‐term galvanostatic cycling stability at RT. As shown in Figure 3h, the Na/SPAN‐NASICON/Na cell delivers a stable cycling performance for up to 500 h at 0.1 and 0.25 mA cm −2 , further confirming the effective suppression of dendrites growth and highly improved cycling stability among anode–electrolyte interface.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the total resistance starts to decrease until cycling at 1.0 mA cm −2 (Figure 3f and Figure S11c, Supporting Information) and ultimately shows a high CCD of 1.4 mA cm −2 , which to our best knowledge is the top‐level among reported NASICON‐based SSEs in published literatures up to now (Figure 3g). [ 37–41 ] It also shows excellent long‐term galvanostatic cycling stability at RT. As shown in Figure 3h, the Na/SPAN‐NASICON/Na cell delivers a stable cycling performance for up to 500 h at 0.1 and 0.25 mA cm −2 , further confirming the effective suppression of dendrites growth and highly improved cycling stability among anode–electrolyte interface.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, a direct strategy of a uniaxial compression loaded on a Na/NASICON assembly was proposed to tackle the interfacial crux. [166] The authors demonstrated that an interstitial layer was formed by pressing the Na metal on the NASICON surface, whereby Chemical pretreatments NaBr 1 m NaPF 6 in EC/PC 1 mA cm −2 ; 1 mA h cm −2 250 cycles 2017 [48] Bi 1 m NaCF 3 SO 3 in diglyme 0.5 mA cm −2 ; 1 mA h cm −2 1000 h 2019 [139] NaI 1 m NaCF 3 SO 3 in diglyme 0.25 mA cm −2 ; 0.75 mA h cm −2 500 h 2019 [140] PhS 2 Na 2 -rich layer 1 m NaPF 6 in EC/PC 1 mA cm −2 ; 1 mA h cm −2 800 h 2020 [141] Na 3 PS 4 1 m NaPF 6 in EC/PC 1 mA cm −2 ; 1 mA h cm −2 270 h 2019 [142] Thin film depositions PEALD-Al 2 O 3 1 m NaClO 4 in EC/DEC 0.25 mA cm −2 ; 1 mA h cm −2 400 h 2017 [144] ALD-Al 2 O 3 1 m NaSO 3 CF 3 in diglyme 3 mA cm −2 ; 1 mA h cm −2 500 h 2017 [61] MLD-alucone Na 3 PS 4 solid-state electrolyte 0.1 mA cm −2 ; 0.1 mA h cm −2 475 h 2020 [145] Free-standing protective films Graphene 1 m NaPF 6 in EC/DEC 2 mA cm −2 ; 3 mA h cm −2 300 h 2017 [146] Carbon paper 1 m NaCF 3 SO 3 in diglyme 5 mA cm −2 ; 1 mA h cm −2 1200 cycles 2018 [147] Others Nano-SiO 2 1 m NaPF 6 in diglyme 1 mA cm −2 ; 1 mA h cm −2 800 h 2019 [148] Ionic membrane 1 m NaClO 4 in EC/PC 0.1 mA cm −2 ; -250 h 2017 [149] Polished Na anode 1 m NaOTf in diglyme 5 mA cm −2 ; 2 mA h cm −2 550 h 2018 [150] Inorganic-organic hybrid protective layer 1 m NaPF 6 in diglyme 2 mA cm −2 ; 1 mA h cm −2 500 h 2019 [152] www.afm-journal.de www.advancedsciencenews.com…”
Section: Inorganic Solid Electrolytesmentioning
confidence: 99%
“…Notably, a direct strategy of a uniaxial compression loaded on a Na/NASICON assembly was proposed to tackle the interfacial crux. [ 166 ] The authors demonstrated that an interstitial layer was formed by pressing the Na metal on the NASICON surface, whereby the interphase layer is of particular importance for intimate interfacial contact and short‐circuit prevention. However, the pressing technique cannot solve the overall issues, especially in some exceptional cases (i.e., the poor pressure toleration of NASICON), which means that multifarious strategies, such as wetting agent introduction, interlayer addition, and anode surface coating, still need to be combined for better anode/electrolyte interfacial contact.…”
Section: Stabilization Of the Sei On Na Metal Anodesmentioning
confidence: 99%
“…It is fortunate that the conductivity of sodium ion conductors (NASICON [5][6][7] , b''alumina [8][9][10] and sulphide 11 ) have been raised to a high enough level, about 10 -4~1 0 -2 S cm -2 , at room temperature, which is approached to that of liquid electrolyte 12 . However, there are still a lot of challenges for solid-state sodium ion batteries, especially the poor wettability between sodium and electrolyte, which will increase the interfacial resistance, promote the side reaction owing to enhanced local polarization, and accelerate dendrite growth [13][14][15] . Thus, how to improve the wettability (or contact) between sodium and electrolyte and ensure a fast charge transport at interface is the key to the development of solid-state sodium ion batteries.…”
Section: Introductionmentioning
confidence: 99%